Protection Evaluation of a Five-Gene-Deleted African Swine Fever Virus Vaccine Candidate Against Homologous Challenge - Xie, Zhenhua; Liu, Yingnan; Di, Dongdong; Liu, Jingyi; Gong, Lang; Chen, Zongyan; Li, Yao; Yu, Wanqi; Lv, Lu; Zhong, Qiuping; Song, Yingying; Liao, Xinxin; et al. (Frontiers in Microbiology, 2022)
African swine fever virus (ASFV) represents a serious threat to the global swine industry, and there are no safe or commercially available vaccines. Previous studies have demonstrated that inactivated vaccines do not provide sufficient protection against ASFV and that attenuated vaccines are effective, but raise safety concerns. Here, we firstly constructed a deletion mutant in which EP153R and EP402R gene clusters were knocked out. Based on the deletion mutant, a further deletion from the MGF_360-12L, MGF_360-13L to MGF_360-14L genes was obtained. The five-genes knockout virus was designated as ASFV-ΔECM3. To investigated the efficacy and safety of the ASFV-ΔECM3 virus as a vaccine candidate, the evaluation of the virus was subsequently carried out in pigs. The results showed that the ASFV-ΔECM3 virus could induce homologous protection against the parental isolate, and no significant clinical signs or viremia were observed. These results show that the contiguous deletion mutant, ASFV-ΔECM3 encompassing the EP153R/EP402R and MGF_360-12L/13L/14L genes, could be a potential live attenuated vaccine candidate for the prevention of ASFV infection.